Hydrothermal synthesis of CeVO4 nanostructures with different morphologies for electrochemical hydrogen storage. Issue 24 (15th December 2021) - Zonarsaghar, Atena; Mousavi-Kamazani, Mehdi; Zinatloo-Ajabshir, Sahar
Abstract: In this paper, CeVO4 nanostructures were produced with controlled hydrothermal method using hydrazine, cerium nitrate, and ammonium vanadate as reactants. Reaction control was performed utilizing hydrazine and ethylenediamine as new reactants. Other effective parameters such as solvent and surfactant were also carefully studied and optimized. The products were then identified through XRD, EDS, FTIR, FESEM, and BET analyses. FESEM results showed that by adjusting the concentration of ethylenediamine, hydrazine, and PVP surfactant, a rod-shaped morphology with suitable porosity could be created. Due to the high potential of CeVO4 in electrochemical processes, it was first employed for electrochemical storage of hydrogen. The amount of hydrogen storage in nanostructures produced with rod-shaped morphology was about 2575 mAh/g, which is very significant compared to products obtained with sodium hydroxide with spherical morphology.